Climate resilient multi-trophic system in Vembanad lake Adaptive Strategy for Enhancement of Clam Fisheries - Paul, Thankam Theresa; Kuberan, G; Panikker, Preetha; Sudheesan, Deepa; Manoharan, S; Usha, U; Sarkar, U K; Das, B K (Indian Farming, 2020)
Vembanad Lake was famous for Black clam (Villorita cyprinoides) resources which has depleted across the years. Thycattussery area had been selected for clam replenishment activity as the 28 ha clam bed area with estimated production of 296.86 kg/ha as reported during 1988-1989 has reduced now to 17 kg/ha. Further, the trophic status of Thycattussery which was estimated at 48.45 indicated an oligo-mesotrophic condition further supporting production enhancements from the system using pens or cages by utilizing the multi-trophic levels in the aquatic ecosystem. The CRPS not only could with stand climatic vagaries but also acted as a carbon assimilation as well as blue carbon sink system. The system has a BCR of 1.28 indicating feasible production system.